Political Economy of Fiscal Unions - Jan Fidrmuc (Center for Economic Studies and ifo Institute (CESifo), 2013)
I formulate a political-economy model of a fiscal union where the threat of secession imposes a limit on fiscal redistribution between regions. I argue that the trade-off between implementing the region's preferred fiscal policy and benefiting from inter-regional risk sharing depends on the nature of economic shocks. Specifically both correlation of shocks across regions and their persistence over time are important. The gains from inter-regional risk sharing are potentially large when shocks are negatively correlated and temporary. In contrast, unions with negatively correlated permanent shocks are likely to prove politically unviable.
Keywords: D72; F59; H77; 330; fiscal federalism; risk sharing; disintegration; median voter; optimum currency areas